Chronology and documentary handbook of the State of Delaware - Frech, Mary L. (Dobbs Ferry, N.Y. : Oceana Publications, 1973)
Includes a chronology of events in Delaware from 1609 to 1970, a biographical directory of prominent people, an outline of the constitution, and copies of pertinent documents.
Bibliography: p. 89.
Keywords: Delaware -- History -- Chronology; Delaware -- History -- Sources; Delaware -- History